Line spectra reduction and vibration isolation via modified projective synchronization for acoustic stealth of submarines - Wen, Guilin; Lu, Yuanzhi; Zhang, Zhiyong; Ma, Chuanshuai; Yin, Hanfeng; Cui, Zhong (Journal of sound and vibration, 2009)
The potential of chaotifying vibration isolation systems to reduce line spectra of underwater vehicle and improve its capability of concealment have recently reported. Notice that for an isolation system, the amplitude of chaotifying vibration is, in general, larger than that of its specified periodic motion subject to the inherent characteristic of chaotic behavior. Therefore, there exists a conflict between the line spectra reduction based on chaotifying vibration responses and the capability of vibration isolation. In this paper, a method based on the modified projective synchronization (MPS) is developed to improve vibration isolation while the chaotifying vibration signals with broad band frequency are utilized to achieve line spectra reduction. The key to this solution is the scaling factors of MPS which enable us to proportionally diminish the vibration amplitudes of the isolated equipment. The feasibility of the methodology in practical engineering is illustrated with the application to acoustic stealth of submarines.